The Effectiveness of Sympathy Appeal as Strategy in Law Case - Wibowo , S. Andika Cahya Ari; Rukmini , Dwi (KnE Social Sciences, 2019)
Sympathy may provide motive which result in why people behave in such a given way. People tend to behave according to what they feel.In law cases in which the suspects have a tendency of difﬁculty proving that he is innocent, the effort to attract public sympathy is then, seen as logical strategy.This article was intended to analyze the effectiveness of sympthy appeal as strategy in law cases. The effectiveness will be analyzedbythecontextof The case of ’bullying’ by Muhammad Arsyad, a satay seller, against President Joko ’Jokowi’ Widodo (2014). It sought causal relation of sympathy appealanditseffectinlegaldecisionthroughlinguisticevidences.Thisstudyemployed Judgement, sub-systems of Attitude in Appraisal devices following a model proposed byMartinandRose(2003).TheﬁndingindicatesthatArsyadeffectivelyusedsympathy appeal as a strategy to mitigate the sentenced. The effectiveness of the sympathy appeal might be proven by these positive judgements provided by the addressee. Keywords: Effectiveness, Sympathy Appeal, Judgement